2017
DOI: 10.1007/s11746-017-3026-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of Oleogel Prepared from Sunflower Oil with β‐Sitosterol and Stearic Acid

Abstract: β‐Sitosterol (Sit) and stearic acid (SA) were combined at varying ratios (w/w) and added to sunflower oil (SFO) at the concentration of 20 g/100 g oil for preparing edible fat‐like oleogel. The oleogel was characterized using an optical microscope, Fourier transform infrared spectroscopy (FTIR), X‐ray diffractometer (XRD), differential scanning calorimeter, and texture analyzer. The oil‐binding capacity, melting temperature, and firmness of the oleogel increased with the increase in the amount of SA in the gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 43 publications
10
57
1
Order By: Relevance
“…An emerging strategy is to design cholesterol‐lowering saturated and trans ‐fat substitutes, which cause unsaturated oils solidified with sterols to form oleogels. This challenging approach is performed by mixing sterols and oleogelators (Han et al ., ; Bin et al ., ; Yang et al ., ). The study of Marangoni () demonstrated the use of sterols and oleogelator structure oils produce components with health benefits in cholesterol‐lowing effect.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…An emerging strategy is to design cholesterol‐lowering saturated and trans ‐fat substitutes, which cause unsaturated oils solidified with sterols to form oleogels. This challenging approach is performed by mixing sterols and oleogelators (Han et al ., ; Bin et al ., ; Yang et al ., ). The study of Marangoni () demonstrated the use of sterols and oleogelator structure oils produce components with health benefits in cholesterol‐lowing effect.…”
Section: Introductionmentioning
confidence: 97%
“…On the molecular scale, tubular structures in Triglyceride (TAG) oils are thought to be formed from sterols and oleogelators, and these tubules aggregate to form a three‐dimensional network (Bot et al ., ; Co & Marangoni, ). Although numerous different oleogelators such as γ‐oryzanol (Arjen & Agterof, ; Rogers et al ., ; Bot et al ., ; Sawalha et al ., ), lecithin (Han et al ., , ), stearic acid (Yang et al ., ), monoglycerides (Bin et al ., ) and triacylglycerols (Acevedo & Franchetti, ) have been proposed for forming phytosterol oleogels, potential oleogelators require further investigation to determine their ability to form structures containing phytosterol in oils. As an oleogelator, beeswax, which contains long‐chain fatty acid esters, can crystallise to form a three‐dimensional network entrapping liquid oil, but still studies of beeswax are relatively limited, particularly those of phytosterol oleogel preparation.…”
Section: Introductionmentioning
confidence: 99%
“…XRD technology can reflect the microcrystalline state of the tested material (Chi et al, 2016;Yang et al, 2017). The XRD patterns of the lutein ester-loaded sunflower oil and the corresponding oleogels with 4, 8, and 12% monostearin formed at 4°C are shown in Figure 3.…”
Section: Xrd Analysismentioning
confidence: 99%
“…A number of studies are devoted to studying the effect of binary mixtures of gelling agents on the properties of fat systems. In particular, the joint effect of β-sitosterol and stearic acid on the microstructure, texture, and thermophysical properties of oleogel with the sunflower oil as dispersion medium is studied in [15]. The interaction between lecithin, monoacylglycerols and phytosterols in the oleogel composition are analyzed, respectively, in [16,17].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%